Commitment Profiles and Voluntary Turnover Intentions : An Empirical Assessment of â€œTwo-Facesâ€ Conceptualization of Normative Commitment - Ramaprasad, Badrinarayan Srirangam; Rao, Shreelatha; Nandan Prabhu, K. P. (Prabandhan: Indian Journal of Management, 2020)
We investigated how affective commitment (AC), continuance commitment (CC), and normative commitment (NC) coalesced to elicit different commitment profiles to differentially exercise their effects on voluntary turnover intentions (VTOI) among 752 information technology (IT) professionals from the Indian IT sector. The key purpose, however, of this research endeavor was to empirically examine the validity of the â€œtwo-facesâ€ conceptualization of NC [i.e. indebted obligation and moral imperative]. The empirical findings, in this connection, first comported to the multi-dimensional nature of organizational commitment (OC) comprising the three components of AC, NC, and CC. Second, the results did not exhibit the presence of high inter-correlation between the construct AC and NC. Third, of the six identified commitment profiles, highly committed [High ACâ€“NCâ€“CC] profile was found to be the strongest in alleviating the VTOI among the IT professionals. VTOI was found to be the most severe in employees who belonged to the least committed [Low ACâ€“NCâ€“CC] profile. Fourth, as regards the construct of NC, the empirical findings of this study offered very little evidence, if any, to support the â€œtwo-facesâ€ conceptualization of NC and comported to the idea of NC as a unidimensional construct that is driven fundamentally by introjected regulation. This is because the construct of NC was not found to alleviate VTOI among employees over and above AC, a fundamental assumption of the two-face theory. Last, the findings of this study did not reveal the existence of high NCâ€“CC commitment profile, thereby casting doubts on whether employees even experience â€˜indebted-obligationâ€™ towards their respective organizations.